Immunomodulatory and antioxidant effects of functional aquafeeds biofortified with whole Laminaria digitata in juvenile gilthead seabream (Sparus aurata) - Marmelo, Isa (2024)
Funding Information: The author(s) declare financial support was received for the research, authorship, and/or publication of this article. This work was supported by Fundação Portuguesa para a Ciência e Tecnologia (FCT I.P.), under the framework of the project Aqua-CLIMADAPT (PTDC/CTA-AMB/0592/2021, https://doi.org/10.54499/PTDC/CTA-AMB/0592/2021) and the “Applied Molecular Biosciences Unit” (UCIBIO) which is financed by national funds from FCT/MCTES (UIDB/04378/2020), the project LA/P/0140/2020 of the Associate Laboratory Institute for Health and Bioeconomy—i4HB. IM also acknowledges FCT I.P. for the PhD grant (2020.04413.BD). Publisher Copyright: Copyright © 2024 Marmelo, Dias, Grade, Pousão-Ferreira, Diniz, Marques and Maulvault.